2022
DOI: 10.1186/s13068-022-02186-y
|View full text |Cite|
|
Sign up to set email alerts
|

Secretion of collagenases by Saccharomyces cerevisiae for collagen degradation

Abstract: Background The production and processing of animal-based products generates many collagen-rich by-products, which have received attention both for exploitation to increase their added value and to reduce their negative environmental impact. The collagen-rich by-products can be hydrolyzed by collagenases for further utilization. Therefore, collagenases are of benefit for efficient collagen materials processing. An alternative and safe way to produce secreted collagenases is needed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Moreover, these cuticular protein genes had covered almost all the cuticular protein families of RR-1, RR-2, Tweedle, CPFL, CPG, and CPH, with the exception of RR-3 [ 25 ]. Intriguingly, another group of molecular structure such as collagens were all down-regulated in mutation of BmMETTL4 ( Figure 7 C), whereas collagenase responsible for degrading native collagen were significantly up-regulated ( Figure 7 D) [ 26 , 27 ]. These analyses indicated important roles of structural proteins in the process of embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these cuticular protein genes had covered almost all the cuticular protein families of RR-1, RR-2, Tweedle, CPFL, CPG, and CPH, with the exception of RR-3 [ 25 ]. Intriguingly, another group of molecular structure such as collagens were all down-regulated in mutation of BmMETTL4 ( Figure 7 C), whereas collagenase responsible for degrading native collagen were significantly up-regulated ( Figure 7 D) [ 26 , 27 ]. These analyses indicated important roles of structural proteins in the process of embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it was found that there were 7 collagenases highly expressed in BmMETTL4 mutant. Collagenases are enzymes with serine hydrolase activity, which are capable of degrading native collagen under physiological conditions [ 27 ]. The significant up-regulation of these enzymes would further destroy the molecular structure activity of collagens.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of amylase-HSA fusion protein disturbed the intracellular redox environment of S. cerevisiae strains, necessitating the production of more byproducts to balance redox cofactors and maintain cell homeostasis. …”
Section: Resultsmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the author noticed an error in Additional file 1: Fig. S5 within the additional information.…”
mentioning
confidence: 99%